2016
DOI: 10.5424/sjar/2016142-8395
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbial functionality in response to the inclusion of cover crop mixtures in agricultural systems

Abstract: Agricultural systems where monoculture prevails are characterized by fertility losses and reduced contribution to ecosystem services. Including cover crops (CC) as part of an agricultural system is a promising choice in sustainable intensification of those demanding systems. We evaluated soil microbial functionality in cash crops in response to the inclusion of CC by analyzing soil microbial functions at two different periods of the agricultural year (cash crop harvest and CC desiccation) during 2013 and 2014.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 49 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…One of the biggest challenges of modern agriculture is the production of enough high-quality food, while reducing the environmental impact and the dependence on external inputs. In this context, cover crops (CCs) have gained popularity as a sustainable alternative with demonstrated beneficial effects on several soil properties (Lu et al, 2000;Chavarría et al, 2016). CCs are defined as crops grown between periods of normal crop production as an alternative to bare soil in fallow months, to provide soil protection and soil improvement (Soil Science Society of America, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…One of the biggest challenges of modern agriculture is the production of enough high-quality food, while reducing the environmental impact and the dependence on external inputs. In this context, cover crops (CCs) have gained popularity as a sustainable alternative with demonstrated beneficial effects on several soil properties (Lu et al, 2000;Chavarría et al, 2016). CCs are defined as crops grown between periods of normal crop production as an alternative to bare soil in fallow months, to provide soil protection and soil improvement (Soil Science Society of America, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that agricultural management has a great influence on cropland SMR [28] . For instance, studies have reported that tillage reduces microbial biomass and their activities, and concurrently disadvantages soil enzymatic activities [29] .…”
Section: Introduction mentioning
confidence: 99%
“…Cover crops (CC) have gained popularity in agricultural practices as a sustainable alternative to fallow between grain crops, to incorporate carbon (C) rich residues in soils and to promote soils coverage, reducing risks of erosion, nitrogen (N) losses, and weeds proliferation [1,2,3]. Among them, rye ( Secale cereale L.), oat ( Avena sativa L.), barley ( Hordeum vulgare L.), ryegrass ( Lolium multiflorum L.) or triticale ( Triticosecale Wittm.…”
Section: Introductionmentioning
confidence: 99%